LIMK1 as a Novel Kinase of β‐Catenin Promotes Esophageal Cancer Metastasis by Cooperating With CDK5 - Shu‐Jun Li; Zhuo‐Ran Liang; Zhi‐Chao Liu; Xue‐Ping Luo; Jun‐Yi Li; Xiao‐Mei Yu; Xuan‐Zhang Huang; Yan He; Tao‐Yang Xu; Jiao‐Jiao Xu; Shao‐Cong Peng; Yu‐Xiang Song; et al. (Advanced Science)
Abstract Metastasis is a major cause of cancer deaths, but the underlying molecular mechanisms remain largely unknown. Esophageal squamous cell carcinoma (ESCC) is a highly aggressive cancer with poor survival, yet the key kinases driving ESCC metastasis and their biological function have not been fully discovered. Here, a kinase‐substrate map of metastatic ESCC is presented for the first time by conducting a phosphoproteomics analysis of 60 clinical specimens. By further consolidating data with CRISPR/Cas9 functional screening, LIM domain kinase 1 (LIMK1) is identified as a novel kinase of β‐catenin. The in vitro and in vivo experiments demonstrated that LIMK1 cooperates with Cyclin‐dependent kinase 5 (CDK5) to promote cancer metastasis in a phosphorylation‐dependent manner. Mechanistically, LIMK1 and CDK5 synergistically phosphorylate β‐catenin at S191, enhancing its phosphorylation and interaction with Nucleoporin 93, resulting in β‐catenin nuclear translocation and activation of key pathways in cancer metastasis. High expression of LIMK1 and CDK5 is associated with poor prognosis of ESCC patients, and the clinical and functional significance of LIMK1/CDK5‐Wnt/β‐catenin axis is also verified in esophageal adenocarcinoma, gastric cancer, and lung cancer. Furthermore, the combination of LIMK1 and CDK5 inhibitors significantly suppresses metastasis in multiple models. This work highlights LIMK1 as a novel regulatory and targetable kinase of β‐catenin, informing the treatment of advanced cancer.